Increased amygdalar metabotropic glutamate receptor 7 mRNA in a genetic mouse model of impaired fear extinction - O’Connor, Richard M. (Psychopharmacology (Berl), 2018)
RATIONALE: Post-traumatic stress disorder (PTSD) is a devastating anxiety-related disorder which develops subsequent to a severe psychologically traumatic event. Only ~ 9% of people who experience such a trauma develop PTSD. It is clear that a number of factors, including genetics, influence whether an individual will develop PTSD subsequent to a trauma. The 129S1/SvImJ (S1) inbred mouse strain displays poor fear extinction and may be useful to model this specific aspect of PTSD. The metabotropic glutamate receptor 7 (mGlu(7) receptor) has previously been shown to be involved in cognitive processes and anxiety-like behaviour placing it in a key position to regulate fear extinction processes. We sought to compare mGlu(7) receptor mRNA levels in the S1 strain with those in the robustly extinguishing C57BL/6J (B6) inbred strain using in situ hybridisation (ISH) in three brain regions associated with fear extinction: the amygdala, hippocampus and prefrontal cortex (PFC). RESULTS: Compared to the B6 strain, S1 mice had increased mGlu(7) receptor mRNA levels in the lateral amygdala (LA) and basolateral amygdala (BLA) subdivisions. An increase was also seen in the hippocampal CA1 and CA3 subregions of S1 mice. No difference in mGlu(7) receptor levels were seen in the central nucleus (CeA) of the amygdala, dentate gyrus (DG) of the hippocampus or prefrontal cortex. CONCLUSIONS: These data show altered mGlu(7) receptor expression in key brain regions associated with fear extinction in two different inbred mouse strains which differ markedly in their fear extinction behaviour. Altered mGlu(7) receptor levels may contribute to the deficit fear extinction processes seen in fear extinction in the S1 strain.